MENTAL ARITHMETIC MOBILE APPLICATION FOR CHILDREN - AZMAN, AUNI KHAIRINA (IRC, 2020)
Children are surrounded by digital technologies that excite and entertain; thus, they spend a lot of time on it in a day. Based on the research, lots of children have negative attitude towards Mathematics as it influences their performance in Mathematics whether as a compulsory subject in school or basic numerical operations like Addition, Subtraction, Multiplication and Division. This arithmetic mobile application research is important to enhance the community awareness on any mobile application used to improve children’s mathematical skill and also increase the selfefficacy in performing Mathematics among them. This project planned to develop an arithmetic mobile application with features that are highly in demand by parents and teachers like reward system and have language options which is Bahasa or English. This application will also contain features like Beginner, Intermediate and Advance level to enhance self-confidence and motivation when user accomplish one level and reach another level